RP HPLC Method for the determination of Tamsulosin in bulk and Pharmaceutical Formulations - Manish Kumar Thimmaraju, Venkat Rao, Hemanth .K, P. Siddartha Kumar (Journal of Applied Pharmaceutical Science)
A simple, sensitive, precise and specific reverse phase high performance liquid chromatographic method was developed and validated for the determination of Tamsulosin in bulk and tablet dosage forms. It was found that the excipient in the tablet dosage forms does not interfere in the quantification of active drug by proposed method. The HPLC separation was carried out by reverse phase chromatography on Shimadzu HPLC, 10-At detector with hypersil ODS C18 Column 250 X 4.6 mm (particle size of 5µ) and constant flow pump. Rheodyne injector with 20 µl loop with a mobile phase composed in the ratio acetonitrile: (0.05M) KH2PO4 buffer (45:55) at flow rate 1.8 ml /min. The detection was monitored at 240nm. The calibration curve for Tamsulosin was linear from 10-50?g/ml and internal standard (Bromhexine) 10?g/ml were prepared by suitable dilutions of the stock solution with appropriate mobile phase. The interday and intraday precision was found to be within limits. The proposed method has adequate sensitivity, reproducibility and specificity for the determination of Tamsulosin in bulk and its tablet dosage forms. LOD and LOQ for Tamsulosin were found to be 0.495 and 0.461.Accuracy (recoveries: 98.5-98.55%) and reproducibility were found to satisfactory.
Keywords: Tamsulosin, RP-HPLC Method, Reverse phase chromatography, bromhexine Acetonitrile, Validation.